The application of molecular data to the phylogenetic delimitation of species in bryophytes: A note of caution - Vanderpoorten, A.; Shaw, A. J. (Phytotaxa, 2014)
Molecular phylogenetics has been of prime importance in revisiting traditional taxonomic hypotheses, and this is especially true in taxa with reduced morphologies like bryophytes. Sequence identity at one or a few loci, as well as evidence for species para-or polyphyly, have been increasingly used to lump species. While sequence identity at loci that are usually variable within the group of interest can provide some incentive for additional study of such species, it does by no means alone provide sufficient evidence for synonymization. Similarly, the strict requirement that all species must be demonstrably monophyletic is equivalent to adopting an uncompromsing view that reproductive isolation (i.e., the biological species concept) is the only valid evidence for species status, and that all species have to be 100% isolated. Some modes of speciation lead to paraphyletic species or even phylogenetic networks. We therefore encourage case by case evaluation of all available data rather than applying a single criterion such as monophyly. We make some suggestions about how to use molecular data in the circumscription of bryophyte species.